Application of MIMIC Model to Construction of Environmental Pressure Index - Jaworska, Renata (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The article aims at estimating the environmental pressure index and provide a ranking for selected European countries with the use of a Multiple Indicators Multiple Causes (MIMIC) model. The MIMIC model is a special form of Structural Equation Modeling able to estimate models with latent variables. This type of model is used to derive information about the relationship between cause and indicator variables and a latent variable, here the index of environmental pressure, from covariance structures. This research analyzes an influence of some causes like GDP per capita, energy efficiency, industrial production, urbanization and working age population as well as the produced electricity from coal sources on the environment. The main indicators of the environmental pressure are C02 and S02 emissions per capita. The index of environmental pressure is finally arrived at with the use of statistically significant causes affecting the quality of the environment. The results of this paper will allow to create a ranking of European countries according to the environmental level. It can be a source of important information for UE environmental policy and for all governments, which closely monitor the environmental performance of individual Member States.